The Palm Collection of UNESP/FCAV - Jaboticabal, Sao Paulo State, Brazil - Pivetta, K. F. L. [UNESP]; Bueno, B. F. [UNESP]; Batista, G. S. [UNESP]; Mazzini, R. B. [UNESP]; Gimenes, R. [UNESP]; Romani, G. de N. [UNESP]; Pimenta, R. S. [UNESP]; Uzzo, R. P.; Tombolato, AFC; Tucci, MLS (Int Soc Horticultural Science, 2013)
The palm collection of UNESP/FCAV, Jaboticabal, Sao Paulo State, Brazil, was created in 1966 with the aim to keep different palm species for research purposes and conservation of native species, especially those threatened. Native and exotic species comprise the collection, which is held at the institution, where several studies with different species and in different areas are undertaken. Nevertheless, palm seeds and seedlings are also distributed to other research centers. The botanical review of the collection began in 2003 and there are, currently, 143 species or hybrids, in a total of 331 specimens. Considering the most ancient species, the immediate identification of many of them was possible; however, for others, such as the Attalea, Orbignya, Syagrus and Scheelea genera, future morphological studies is required, like the karyotype one or using molecular markers. Many species have been introduced and many seeds have been currently investigated regarding their germination process for future inclusion in the collection. Some of the palms do not bloom; others, however, bloom, but do not bear fruits; and others bear fruits, but their seeds do not germinate. They are either young plants, fruits which are constantly attacked by insects, like the Syagrus species and hybrids, or dioecious plants.
Keywords: genetic resources; seed source; ornamental; palms